A network analysis of psychological flexibility, coping, and stigma in dermatology patients - Vasiliou, Vasilis S.; Russell, Hellen; Cockayne, Sarah; Coelho, Gabriel Lins de Holanda; Thompson, Andrew R. (Frontiers in Medicine, 2023)
Despite the long-reported negative effects of stigma in individuals with skin conditions, interventions to address its effects are rare. This might be in part due to a continued lack of understanding as to how individuals respond to stigma and how this response leads to less stigmatized experiences. We need to leverage new methods that map how individuals cope with stigma and how this coping relates to less stigma experience or suffering. In this study, we employed a step-case analytic method, using traditional regression, moderation, and the newest network analyses, to examine the role of psychological flexibility (PF) with stigmatized experiences, and stigma-related outcomes. We run a cross-sectional study (n=105 individuals with various skin conditions) and analyzed stigma-related variables. We included variables examining perceived stigmatization (PSQ), anxiety (GAD-7), depression (PHQ-9), well-being (EQ5D5L), and variables stemming from the PF model (CompACT), presented as three coping with stigma responses, namely “open”, “aware”, and “active”. Using network analysis, the most influential or central variables that contributed to stigma were generalized anxiety, perceived stigmatization, and valued actions. In relation to PF, being open to the experience of stigma (as opposed to avoidance), keeping a distance from stigmatized thoughts (as opposed to self-stigmatizing), and bringing attention to value-based committed actions (as opposed to passivity) were all found to contribute to less stigmatized experiences. The results indicate that two of the three skills of the PF model (“open” and “active”) may be important targets for interventions targeting stigma alleviation in people living with skin conditions.